Training Mothers on Complementary Feeding Preparation and Toddler Growth Screening at Olak Kemang Health Center - Harahap, Huntari; Aurora, Wahyu Indah Dewi; Hanina, Hanina; Ekaputri, Tia Wida; Ayudia, Esa Indah (Scientific Of Environmental Health and Diseases, 2025)
Background: Proper complementary feeding is crucial for optimal child growth and development. However, many mothers lack knowledge about the correct preparation, timing, and nutritional composition of complementary feeding, increasing the risk of malnutrition and stunting in toddlers. This community service program aimed to enhance maternal knowledge on complementary feeding and conduct growth and development screenings for toddlers. Method: The program was conducted at Olak Kemang Health Center and involved 15 mothers and their children. The intervention included hands-on training led by nutrition experts on the proper preparation and nutritional composition of complementary feeding. Additionally, toddlers underwent growth and development assessments using anthropometric measurements and the Pre-Screening Questionnaire for Development (KPSP). Result: The majority of toddlers (73.33%) had normal nutritional status, while 13.33% were underweight and 13.33% were overweight. Growth and development screening showed that 93.3% of toddlers demonstrated normal development, whereas 6.67% had developmental delays. The training significantly improved mothers' knowledge of complementary feeding preparation. Conclusion: Regular educational programs are essential to improve maternal knowledge on complementary feeding and enhance early childhood growth monitoring. These efforts can help reduce the risk of malnutrition and stunting among toddlers.